Development of an Innovation Model of Public Service In Education Management For The Disadvantaged Children of Local Government Organizations in the Area of Thai - Malaysian Border - Dumkool, Arunrat; Ploywan, Phut; Sirisunhirun, Somboon (Journal of Ecohumanism, 2025)
Background: Public service in education management plays a crucial role in ensuring that disadvantaged children have access to quality education and the opportunity to reach their full potential. Objectives: 1. To identify the factors that promote the quality of public services in education management for the disadvantaged children. 2. To develop innovative public service models in education management and policy recommendations to increase educational opportunities for disadvantaged children in local administrative organizations in the Thai-Malaysian border area. Methods: This study utilized mixed-method research. The quantitative phase was characterized by an initial quantitative phase of data collection by the questionnaire with 143 people from 61 Songkhla Province, 51 people from Narathiwat Province, 31 people from Satun Province by selecting through non-probability sampling by Quota methods was used for defining the sample. Then, the qualitative phase collected the data from15 participants from group of executives, academics, experts, officials, and related people in the area in the southern border provinces. Participants were recruited using purposive sampling. Results: The result of the quantitative phase showed that there was no influence on the priority on the quality of public services in education management for disadvantaged children groups of local government organizations. The qualitative found the model of public service in education management for disadvantaged children of local government organizations in the area of the Thai-Malaysian border consists of formal education, a model aimed at direct access to children, establishment of specific institutions or special schools suitable for groups of disadvantaged children, and combination of multiple models for a comprehensive service.